Jender dalam Pandangan Islam - M. Hasbi Amiruddin (Universitas Islam Negeri Ar-Raniry, 2001)
Different in their nature, men and women are not treated unequally in Islam. Several writings that suggest the limited nature of women's activities constitute the outcomes of certain environments. History shows us that in many Moslem world women enjoy their involvement in various undertakings under the umbrella of Islam.